Partição de recursos entre seis espécies de Loricariidae no alto rio Paraná, na região de Guaíra-Pr : distribuição espacial, morfologia e ecologia trófica. - Delariva, Rosilene Luciana (1997)
This study were approached the spatial distribution, morphology and feeding ecology of six species of Loricariidae during the period August 1996-April 1997, in an area approximately 4 Km, at the Paraná River, including the upper portion of former Sete Quedas waterfalls. For the analysis of spatial distribution, the fishes were catched with castnets commercial fishery from 17 to 22 April 1997. The morphology, biometry and feeding information's were obtained of the fishes captured monthly from August 1996 to April 1997, using the same fishery strategy. Multivariate analyses (Cluster Analysis, Dentrended Correspondence Analysis) were used to examine the similarity patterns of different attributes (distribution, morphology and feeding) among the species. The spatial distribution was related with difference in the substrate type and depth. R. aspera and H. ternetzi showed preference for heterogenic bottom and deeper environments. H. regani and H. margaritifer distributed in shallower areas independent of substrate type, and M. Aculeatus e H. microstomus were more abundant in shallower areas with homogeneous substrate. In general, the six species showed two forms of food intake, for sucking (R. aspera) and browsing (the others). These feeding tactics were related with the differences morphological characters of the feeding apparatus. R. aspera has a morphology adapted to the consumption of high quantity of organic detritus as well as high length gut and gills rakers well developed while that others explore aufuwchs using their cuspited and in scoop form teethes. High value of feeding overlap were registered just among M. aculeatus X H. microstomus and R. aspera X A. regani. For the others congenerics species the value were under of 50.0. So, the feeding specialization as well as the spatial segregation's must represent important role in the separation of the trophic niche among these species avoiding high competitive pressure.